KEARIFAN LOKAL-GLOBAL DALAM DONGENG DARI BERBAGAI NEGARA - Hirmawan Wijanarka (Sintesis, 2019)
This research aims at observing local wisdoms revealed in folktales from various areas/countries, andhow these local wisdoms make up global wisdoms. Twenty nine (29) folktales from various differentareas/countries (or communities) are observed. The folktales chosen are expected to represent variouslocal wisdoms from different areas/countries in the world. These folktales have all been rewritten andtranslated into English, and are collected in The Greedwood Library of World Folktales (Volume 1 Volume 4), edited by Thomas A. Green, published in 2008. This study results in two major findings.Firstly,the folktales show that there are similar (or even the same) local wisdoms in most part of theworld. This research comes up with fourteen (14) local wisdom simplied in the folktales. Secondly,outof these fourteen local wisdoms, four global wisdoms that underlie the local wisdoms are found.